2015
DOI: 10.1002/2015gb005097
|View full text |Cite
|
Sign up to set email alerts
|

Ocean nutrient pathways associated with the passage of a storm

Abstract: Storms that affect ocean surface layer dynamics and primary production are a frequent occurrence in the open North Atlantic Ocean. In this study we use an interdisciplinary data set collected in the region to quantify nutrient supply by two pathways associated with a storm event: entrainment of nutrients during a period of high wind forcing and subsequent shear spiking at the pycnocline due to interactions of storm-generated inertial currents with wind. The poststorm increase in surface layer nitrate (by~20 mm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
47
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(53 citation statements)
references
References 40 publications
5
47
1
Order By: Relevance
“…These results are qualitatively similar under the weaker stress, but the changes in column‐integrated ⟨ N ⟩ x , y and ⟨ P ⟩ x , y are about 1/3 to 1/2 as large, which is qualitatively consistent with less deepening of the MLD 3 and less nutrient entrainment under weaker wind stress (Figure S5). In addition, this evolution is qualitatively consistent with expectations based on available observations of the nutrient and/or chlorophyll responses to autumn storm passage (e.g., Babin et al, ; Rumyantseva et al, ).…”
Section: Resultssupporting
confidence: 89%
See 1 more Smart Citation
“…These results are qualitatively similar under the weaker stress, but the changes in column‐integrated ⟨ N ⟩ x , y and ⟨ P ⟩ x , y are about 1/3 to 1/2 as large, which is qualitatively consistent with less deepening of the MLD 3 and less nutrient entrainment under weaker wind stress (Figure S5). In addition, this evolution is qualitatively consistent with expectations based on available observations of the nutrient and/or chlorophyll responses to autumn storm passage (e.g., Babin et al, ; Rumyantseva et al, ).…”
Section: Resultssupporting
confidence: 89%
“…It is difficult to observe all the variables and spatiotemporal scales necessary to evaluate the hypotheses emerging from these simulations, but there are many observations of the bio‐optical and physical response of the upper‐ocean to a summer or autumn storm from satellites (e.g., Babin et al, ; Carranza & Gille, ; Fauchereau et al, ; Lin et al, ; Lin, ) and a rapidly increasing but small number of subsurface bio‐optical observations during and after storms from profiling subsurface floats (e.g., Chacko, ; Girishkumar et al, ; Ye et al, ). Like all our simulations, many of these prior observations, including the observations of Rumyantseva et al () and Painter et al (), which motivated the present study, show that autumn storms increase the surface density, deepen the mixed layer, erode subsurface chlorophyll maxima and mix subsurface chlorophyll up toward the surface (thereby increasing the fraction of column‐integrated chlorophyll in the mixed layer), and trigger an increase in column‐integrated chlorophyll. However, the magnitude and qualitative nature of these responses are highly variable between different storms (see, e.g., Painter et al, ) due to the wide variety of different physical and biogeochemical circumstances in which storms occur.…”
Section: Conclusion and Discussionsupporting
confidence: 87%
“…If the surface layer is stirred by strong wind and mixed with the subsurface low pCO sea 2 layer, the surface will act as a further CO 2 sink. Several reports indicate that the strong wind associated with the passage of low pressure systems deepens the surface mixed layer and has impacts on the biogeochemistry (Wada et al, 2011;Rumyantseva et al, 2015). Simmonds and Keay (2009) reported that the strength of cyclones in the Arctic Ocean is increasing with the long-term reduction of sea-ice cover.…”
Section: Future Direction Of Hidden Co 2 Sink In the Canada Basinmentioning
confidence: 99%
“…According to the turbulence activity parameter, the intermediate regime of turbulence dominates between the base of the SML and the 1,026.2 isopycnals (not shown). At those depths, vigorous patches of κρ play an important role in the turbulent flux of conservative and nonconservative properties, which can be estimated from Fc=κρCz, where Cfalse/z is the vertical gradient of a scalar property C (e.g., Doubell et al, ; Kaneko et al, ; Rumyantseva et al, ).…”
Section: Turbulence Observationsmentioning
confidence: 99%
“…Chlorophyll‐a fluorescence is the most commonly used index of phytoplankton biomass which is controlled primarily by the nutrient (nitrate) transport within the ocean (Sarmiento & Gruber, ). The density‐nitrate relationship was applied to the microstructure‐derived density to estimate the microscale vertical distribution of nitrate (e.g., Rumyantseva et al, ; Sharples et al, ). One advantage of having a reliable density‐nitrate relationship is that measurements of the nitrate gradient and turbulent diffusivity can be obtained via the same instrument at the same time.…”
Section: Turbulence Observationsmentioning
confidence: 99%